GANGGUAN KESEIMBANGAN PADA PENDERITA PASKA STROKE DENGAN SKALA KESEIMBANGAN BERG - Martin Firman Suryo*, Salim Harris*, Freddy Sitorus* (Neurona Majalah Kedokteran Neuro Sains, 2011)
INTRODUCTIONONE OF THE MOST COMMON PROBLEMS AMONG STROKE PATIENTS IS IMBALANCE THE PATIENTS WHO EXPERIENCED THIS WOULD USUALLY FEEL INSECURE AND HAVE INCREASE IN DEPENDENCY ONE OF THE TREATMENT GOALS IS TO STIMULATE THE PATIENT TO BECOME MORE INDEPENDENT BECAUSE EVENTHOUGH THEY ARE IN GOOD HEALTH WITH NO OTHER ILLNESSES THE PATIENTS WITH IMBALANCE COULD BECOME VERY DEPENDENT